EDGE EFFECTS AND EXTERIOR INFLUENCES ON BUKIT TIMAH FOREST, SINGAPORE - 48– 61 M CHATTERJEA (European Journal of Geography)
Bukit Timah Nature Reserve in Singapore, a 163 sq km lowland tropical rainforest, is surrounded by dense urban residential development. The forest peripheral areas are characterized by open, concrete-covered surfaces of car parks, high-rise buildings, and wide highways. Although some areas around the peripheries are covered with buffer vegetation, the forest interior environment is influenced by the non-forested landcovers around. This research investigates four specific factors, such as atmospheric temperature, relative humidity, soil temperature, and wind velocities in the interior forests, buffer areas as well as the forest boundaries. The aim is to ascertain the degree of changes in these factors due to landcover changes and also to determine the extent of influences these exert on the forest interiors. Steep gradients of environmental changes across the forest have been established and several hot spots with intense alterations of environment have been demarcated, although the forest interiors still retain the original microclimatic conditions of a typical rainforest. Such assessments are useful in efforts to manage and maintain forest interior integrity.